2012
DOI: 10.1098/rstb.2011.0314
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of nitrogen application rates on the activity and diversity of denitrifying bacteria in the Broadbalk Wheat Experiment

Abstract: Bacterial denitrification results in the loss of fertilizer nitrogen and greenhouse gas emissions as nitrous oxides, but ecological factors in soil influencing denitrifier communities are not well understood, impeding the potential for mitigation by land management. Communities vary in the relative abundance of the alternative dissimilatory nitrite reductase genes nirK and nirS , and the nitrous oxide reductase gene nosZ ; however, the sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 38 publications
(74 reference statements)
7
50
3
1
Order By: Relevance
“…Nitrate reduction by denitrification is of great importance because it can lead to considerable nitrogen losses in agriculture and emissions of greenhouse gases (Cheneby et al, 2009). In general, activity of this process increases with soil temperature and moisture and is strongly dependent on soil physiochemical properties especially on soil organic carbon content (Szukics et al, 2010;Clark et al, 2012;Miller et al, 2012). According to the findings of Cheneby et al (2009), nitrate reduction activity was stimulated by combined organic and mineral fertilization but not by organic fertilization alone.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Nitrate reduction by denitrification is of great importance because it can lead to considerable nitrogen losses in agriculture and emissions of greenhouse gases (Cheneby et al, 2009). In general, activity of this process increases with soil temperature and moisture and is strongly dependent on soil physiochemical properties especially on soil organic carbon content (Szukics et al, 2010;Clark et al, 2012;Miller et al, 2012). According to the findings of Cheneby et al (2009), nitrate reduction activity was stimulated by combined organic and mineral fertilization but not by organic fertilization alone.…”
Section: Resultsmentioning
confidence: 98%
“…Denitrifying bacteria are more numerous than any other functional groups involved in the nitrogen cycle (Clark et al, 2012). Nitrate reduction by denitrification is of great importance because it can lead to considerable nitrogen losses in agriculture and emissions of greenhouse gases (Cheneby et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, a good agreement was observed between modelled and measured yield, except for the plot with no nutrient input (control plot). In spite of no fertilizer application, a yield increase in the control plot has been observed (Clark et al 2012;Powlson et al 2014), which, it has been proposed, could be due to atmospheric N deposition of around 35-45 kg N ha -1 a -1 . Including N deposition in DDC tends to reduce the gap between modelled and measured yield, but could not explain the entire gap between modelled results and observations.…”
Section: Modelled Soc and Yieldmentioning
confidence: 96%
“…Due to practical limitations, not all parameters could be measured each year and we used our previous experience (Hirsch et al 2009;Clark et al 2012) to plan sampling to cover the most relevant periods of change. A randomised sampling grid was designed at the outset of the conversion to provide 160 sampling areas of 0.25 m 2 to ensure that no part of each plot was sampled more than once and different assays did not interfere.…”
Section: Soil Samplingmentioning
confidence: 99%
“…DNA samples and PCR results failing to meet our quality criteria were discarded: a full description of the primers, PCR conditions and quality controls has been described previously (Cardenas et al 2013;Clark et al 2012) and is provided in the Supplementary Information. We did not quantify archaeal 16S rRNA genes: previous results indicated that they were 100-times less frequent than bacteria in our soils and the vast majority were ammonia oxidizers, so would be enumerated by the primers for archaeal amoA (Zhalnina et al 2013).…”
Section: Soil Samplingmentioning
confidence: 99%